Analisis Keberfungsian Sosial Mahasiswa Yang Aktif Berorganisasi: (Studi pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sumatera Utara) - Muhammad Fadhlan Amri; Randa Putra Kasea Sinaga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
college students have a significant role and influence, as well as a significant contribution to various areas and in the midst of social life. The role they have, college students certainly have a number of social functions in society, which are generally fulfilled and carried out by utilizing the presence of student organizations in each faculty. The main informants in this study active FISIP USU college students who were also active in internal and external campus organizations. Additional informants consisted of one FISIP USU lecturer, as well as a key informant who was the Deputy Dean I of FISIP USU who oversaw Academic, Student Affairs and Alumni and directly interacted with college student and organizational activities at FISIP USU. The data collection technique in this study was carried out by merging (triangulation) of in-depth interviews, observations, and documentation. Data will be analyzed by the researcher qualitatively and ended with drawing conclusions from the research results that have been conducted. The aim of this study to find out and analyze how the role and social functioning from students who are active in organizations in the Faculty of Social and Political SciencesUniversity of Northern Sumatra.The results of the study showed that there were already efforts by active college student organizations in FISIP USU to carry out their social functions, but there were differences in the ability to perform their social functions, both from internal student organizations such as the Department Student Association, to external campus organizations such as HMI and KMK, even though in their implementation there were still strengths and weaknesses of internal and external organizations..